The scope of acceptance by patients motherly and friendly style of nurse’s supporting behaviour in palliative care - Chmiel, Izabela; Górkiewicz, Maciej (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. The patients’ reactions to care-providers, as well as patients’ demographic and clinical features, not always provide the sufficient basis for concluding about their preferences, because of patents’ specific situation. Aim of the study. At this study the subject was restricted to easy observable nurse’s touch. Evidence on patients’ acceptance of motherly and friendly style of behaviour in palliative care. Material and methods. The answers 35-item questionnaire were obtained at study group of 55 patients in the terminal stage of cancer. Results. Each patient under study expected and experienced the nurse’s touch; 55 (95%) patients are satisfied with obtaining an instrumental touch, 51 (93%) - with caring touch, 50 (91%) - with communicating touch, 53 (96%) - with healing touch. Similar results were obtained for the kin’s and doctors’ touch. Considering the healing touch, 32 (58%) patients accept friendly style but don’t accept motherly touch, 19 (35%) accept both styles. The above patients’ groups don’t differ significantly in their demographic and clinical features. Conclusions. Among patients in terminal stage of cancer, there are significant differences in individual preferences concerning the style and form of supporting behaviour of care-providers. The patient’s demographic and clinical features, his reaction to experiencing touch don’t provide sufficient basis for conclusions about their preferences, therefore, the interviews carried out at another time by other persons are necessary. Thus, the obtained results confirm the necessity of continuation of the studies of the means of achieving compliance between the nurses’ behaviour and patients’ preferences. Nursing Topics 2010; 18 (4): 399-405